Conspectus of the Phlaeothripinae genera from China and Southeast Asia (Thysanoptera, Phlaeothripidae) - Dang, Li-Hong; Mound, Laurence A.; Qiao, Ge-Xia (Zootaxa, 2014)
An illustrated identification key is provided to 100 genera of Phlaeothripinae from China and Southeast Asia, together with a diagnosis for each genus, and comments on the species diversity. One new genus with a new species, Akarethrips iotus gen.n. & sp.n., and two new species, Heliothripoides boltoni sp.n. and Terthrothrips strasseni sp.n., are described from specimens collected in Peninsular Malaysia and Java respectively. Three Phlaeothripinae genera are synonymised, Mychiothrips Haga & Okajima syn.n. of Veerabahuthrips Ramakrishna, Syringothrips Priesner syn.n. of GigantothripsZimmermann, and Sauridothrips Priesner syn.n. of Gynaikothrips Zimmermann. In addition, four nomenclatural changes are included, Adelphothrips ignotus (Reyes) comb.n. transferred from Mesothrips, Karnyothrips palmerae (Chen) comb.n from Xylaplothrips, Xylaplothrips bogoriensis (Karny) comb.n from Brachythrips, and Oidanothrips notabilisFeng, Guo & Duan considered as a new synonym of Oidanothrips frontalis (Bagnall).